Foreign Language learning and teaching Enjoyment: Teachers’ Perspectives - Mierzwa, Ewelina (Journal of Education Culture and Society, 2019)
Aim. The primary objective of the present study was to investigate the level of Foreign Language learning Enjoyment and Foreign Language teaching Enjoyment experienced by foreign language teachers in Poland. The secondary aim of the study was to investigate the sources of FLE from the perspective of FL teachers. Methods. The informants of the study were Polish educators teaching foreign languages at different educational levels (from primary to tertiary education). To compute the obtained quantitative data, the statistical program STATISTICA was used. Standard descriptive and inferential statistics were used to report means, median and standard deviation for sociodemographic and baseline characteristics of the sample. The t-Test and one-way ANOVA were used to show mean differences in the score data.Results. The results of the study revealed that foreign language teachers experienced a relatively high lvel of both Foreign Language learning Enjoyment) and Foreign Language teaching Enjoyment (FL teaching Enjoyment), regardless of independent variables (e.g. place of residence, level of education, language being taught, the years of experience). The result revealed a significant gender difference in FL learning Enjoyment in favor of females, while there was no gender difference in FL teaching Enjoyment. A qualitative analysis of participants’ emotional experiences in FL classroom confirmed previous research on FLE to a certain degree. That is, FLE is more related to learner-internal and teacher-specific variables than to the behavior of the peers and the atmosphere created in the FL classroom.Conclusion. The originality of the present study lies in the choice of a mixed method approach (both of a qualitative and quantitative nature) using a relatively large sample in a field characterized by case studies. To the best of my knowledge, this is the first study on foreign language enjoyment among teachers within the Polish educational context.